Menggali Himpunan Kearifan Lokal: Perspektif Teori Himpunan Dalam Budaya Papua - Muhimatus Shofiyani; Cici May Linda; Nagita Dessy Fitrianingsih; Satria Panji Nugraha; Sholeh Widodo; Siti Aminah; Prihaten Maskhuliah (Lembag, 2025)
Local wisdom is an essential element in understanding the cultural identity of a society. In Papua, local wisdom encompasses knowledge, values, and practices that have been passed down through generations. This article discusses the importance of exploring and preserving local wisdom in Papua, as well as the challenges posed by globalization and climate change. By employing a set theory approach, the author analyzes how local wisdom can be categorized and understood within a broader cultural context. Through education and collaboration, it is hoped that local wisdom can continue to thrive and contribute to sustainable development.